Physiological Responses to Firefighting in Extreme Temperatures Do Not Compare to Firefighting in Temperate Conditions - Windisch, Stephanie; Seiberl, Wolfgang; Hahn, Daniel; Schwirtz, Ansgar (Frontiers in Physiology, 2017)
Purpose: The aim of this study was to examine physiological responses to two different simulated firefighting exercises: a firefighting exercise with flashovers, smoke, poor visibility and extreme temperatures (300°) in a burning container and a standard firefighting exercise in temperate conditions. Furthermore, a second purpose of the study was to find out if the contribution of strength and endurance capacities to firefighting performance changes when the demands of the firefighting exercise change. Methods: Sixteen professional firefighters performed a maximum treadmill test, strength testing, a standard simulated firefighting exercise (SFE) without heat and flashovers and a firefighting exercise with a simulation of the flashover phenomenon in a burning container (FOT). The treadmill testing was used to determine peak oxygen uptake (VO2peak), ventilatory threshold (VT1) and respiratory compensation point (RCP). Three intensity zones were identified according to heart rate (HR) values corresponding to VT1 and RCP: zone 1–HR below VT1, zone 2-HR between VT1 and RCP, zone 3–HR above RCP. Firefighting performance was determined by a simple time-strain-air depletion model (TSA) taking the sum of z-transformed parameters of time to finish the exercise, strain in terms of mean heart rate, and air depletion from the breathing apparatus. Correlations were then established between TSA based firefighting performance parameters and fitness variables representing strength and endurance. Results: HR was significantly lower during SFE (79.9±6.9 %HRmax) compared to FOT (85.4±5.2 %HRmax). During SFE subjects spent 24.6±30.2 % of time in zone 1, 65.8±28.1 % in zone 2 and 9.7±16.6 % in zone 3. During FOT subjects spent 16.3±12.8 % in zone 1, 50.4±13.2 % in zone 2 and 33.3±16.6 % in zone 3. Out of all correlations, relative VO2peak showed the highest relation to mean HR during SFE (-.593) as well as FOT (-.693). Conclusions: Endurance in terms of VO2peak is an important prerequisite for both firefighting exercises. However, for standard simulated firefighting exercises it is important to work below VT1. For firefighting exercises in extreme temperatures with smoke, poor visibility and unexpected flashovers a high fitness level is required in order to keep the time spent above RCP as short as possible.